Current Strategies of Sustainable Development and Environmental Protection in the CIS Countries (KIUT Publication, 2025)
The rapid deterioration of the environment caused by irrational economic activity negatively affects socio-economic development. This leads to reduced employment, increased poverty, and social vulnerability, which confirms that the economy is only a part of the ‘human–nature–society’ system, where changes in one element affect the others.